A SYSTEM OF WASTE UTILIZATION WITH PROCESSES OF BIOLOGIC AND THERMIC DESTRUCTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
There are prognoses that wast mass will increase in the near future. Over half of waste mass makes various nature organic waste .At present waste is buried in landfill, partly recycled traditionaly by composting or utilized in biocells with collecting and employing of biogas. In this article considered conditional region (town and ambience willage )waste utilization with environment friendly modern biotechnology and traditional thermal process Liquid concentrated organic waste is recycled in closed biogas equipment, solid waste is burnt in gasification type furnace. Combining this equipment in complex is possible efficiently use energy obtained from waste. Examined influence of integrated processing system to environment, material and energy cyclization, efficiency employ of obtained energy and processing system comparing with waste burying in landfill.